HUBUNGAN ANTARA DUKUNGAN KELUARGA DENGAN UPAYA PREVENTIF KEJADIAN HIPERTENSI PADA LANSIA - Arbianto, Wahyu Adi; Adriani, Prasanti; Novitasari, Dwi (Coping: Community of Publishing in Nursing, 2023)
Elderly is defined as a person who is over 60 years of age. Elder is someone who is more than 60 years old. Hipertensi often terjadi without any symptoms. This condition make a bigger the risk of stroke, heart Ace and kidney there are several things that are needed by people with hipertention such as support from the family whichis provide in the form of material, information, advice and real assistance. The purpose of this research to analyze the relationship between family support and preventive measures against the incidence of hypertension in the elderly in the South Purwokerto Health Center area. This type of research is quantitative with descriptive design and cross sectional approach. The population in this study were elderly 60 years old and over in the working area of ??the Puskesmas south Purwokerto with a total of 209 people, using purposive sampling technique and setting the Slovin formula so that the number of samples in this study was 137 respondents. The instrument used is a questionnaire using a Likert scale about family support and prevention of hypertension. The data analysis used was univariate analysis in the form of age, gender, education level, family support, and bivariate analysis using the Sperman-Rank test. The results obtained p-value (0,0001) and Rho value (0,391) which means there is a relationship between family support and prevention of hypertension.